Refinancing under Yardstick Regulation with Investment Cycles–The Case of Long-Lived Electricity Network Assets - Dominik Schober (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2013)
In the context of yardstick regulation with long-lived assets, the influence of investment cycles and thereof resulting heterogeneous capital structures on the ability to recover capital is quite important. Investment decisions are based on whole investment cycles of the infrastructure. It is shown in this article that variable lifetimes of assets may cause substantial problems of capital-recovery under an efficient firm standard yardstick regulation based on historic (straight-line) depreciation. Resulting heterogeneous investment and cost cycles may cause instantaneous yardstick levels below the long-run refinancing level. Recovery is neither possible in later periods because of the efficient firm standard. An illustrating empirical example is used to demonstrate the relevance of the problem. Finally, two alternatives, branch average cost yardstick determination and correction factors based on the share of capital under depreciation, are discussed.
Keywords: L51; L52; 330; Electricity markets; yardstick regulation; benchmarking; infrastructure investment; capital-recovery; sustainable refinancing